1976
DOI: 10.1073/pnas.73.1.198
|View full text |Cite
|
Sign up to set email alerts
|

Novel F prime factors able to replicate in Escherichia coli Hfr strains.

Abstract: A novel type of F' plasmid that can replicate extrachromosomally in celLs of Hfr strains has been isolated. Genetic analysis of these plasmids indicates that all carry the dnaA-bgIA region of the E. coli chromosome as well as ilv+ used as a selective marker. It is suggested that a specific site, designated pohd (permissive on Hfr), is located -in this region, and is essential for these plasmids to replicate in Hfr cells. The most interesting explanation, among others, would be that the poh+ site represents the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Initiation of chromosome replication in Escherichia coli occurs at a fixed point, oriC (Marsh and Worcel, 1977). Minichromosomes are plasmids that replicate autonomously from oriC (Hiraga, 1976; Messer et al ., 1978; von Meyenburg et al ., 1979). They depend on functional DnaA and DnaC products, de novo protein synthesis and RNA polymerase mediated transcription for initiation of bi‐directional replication, thereby resembling their chromosomal counterparts (for review see Messer and Weigel, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Initiation of chromosome replication in Escherichia coli occurs at a fixed point, oriC (Marsh and Worcel, 1977). Minichromosomes are plasmids that replicate autonomously from oriC (Hiraga, 1976; Messer et al ., 1978; von Meyenburg et al ., 1979). They depend on functional DnaA and DnaC products, de novo protein synthesis and RNA polymerase mediated transcription for initiation of bi‐directional replication, thereby resembling their chromosomal counterparts (for review see Messer and Weigel, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Initiation of chromosome replication occurs at a unique site on the chromosome, termed oriC (8). The process involves several proteins, including DnaA protein encoded by the dnaA gene.…”
mentioning
confidence: 99%
“…Hiraga then demonstrated that this region of chromosomal DNA, when carried on F’ plasmids, was sufficient to suppress incompatibility of F plasmids to replicate in Hfr strains (105). He first called this region poh + , (permissive on Hfr) and then named the genetic locus “ oriC ” to designate the ori gin of c hromosome replication (105). OriC was more precisely mapped to be in, or near a 1.3 kb Hind III fragment located at 84.3 minutes on the E. coli chromosome (161).…”
Section: An Abbreviated Historymentioning
confidence: 99%